2007
DOI: 10.1557/proc-0990-b09-09
|View full text |Cite
|
Sign up to set email alerts
|

Study of Fatigue Behavior of 300 nm Damascene Interconnect Using High Amplitude AC Tests*

Abstract: The AC fatigue test technique, which uses cyclic joule heating to apply thermal cycles to thin-film structures, was applied to copper lines and vias in damascene dielectric structures on silicon substrates. Specimen chips with two different types of dielectric, oxide and low-k, were tested. The lines were 300 nm wide; various via widths were tested. At 100 Hz, cyclic temperature ranges from 400 to 900 ∫C produced line lifetimes between 10 and 1 million seconds. Similar lifetimes were reached in the vias for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Practically all of the studies to date on cyclic Joule heating have reported on unconstrained conductive metal lines on substrates, but some studies of buried lines have been reported [12,15,18,19]. The behaviour of conductors buried within a dielectric structure is expected to be influenced by the constraint exerted by the surrounding structure.…”
Section: Introductionmentioning
confidence: 99%
“…Practically all of the studies to date on cyclic Joule heating have reported on unconstrained conductive metal lines on substrates, but some studies of buried lines have been reported [12,15,18,19]. The behaviour of conductors buried within a dielectric structure is expected to be influenced by the constraint exerted by the surrounding structure.…”
Section: Introductionmentioning
confidence: 99%